(untitled) (Revista de Ensino em Artes, Moda e Design, 2023)
Abstract This article discusses the creation of Schools for Artificer Apprentices and Professional Education in the 19th century, which gave rise to the Professional Technical Schools in the state of São Paulo in the early 20th century. With the growth of cities at the turn of the century, motivated by factory workers and newly arrived immigrants, the impact on the city of São Paulo was significant, motivating the state government to meet the new urban and social needs and, to redefine the processes of instruction for the formation of qualified labor, beyond gender roles, in this social configuration. We researched from the Professional Schools for Women and Men (1911), in the capital of São Paulo, the expansion of a significant network of professional schools created in the interior of the state, such as Sorocaba, Franca and Ribeirão Preto. The result of the research confirmed the hypothesis that these institutions and courses, through the knowledge generated and the specific knowledge destined for men and women, are at the base of the training of superiors who constituted the universe of Fashion and Fashion Design, at the end of the 20th centuryin Brazil.